Modulatory efficacy of bone metabolism and safety of denosumab versus zoledronic acid in the treatment of bone and joint osteoporosis in elderly men - He, Jing; Mao, Yuhui; Gong, Wanran; Zhu, Haitao; Xiang, Peng; Wang, Shui; Dai, Xiaofeng (Frontiers in Pharmacology, 2025)
ObjectiveThis study aimed to compare the clinical efficacy and safety of denosumab versus zoledronic acid (ZA) in the treatment of osteoporosis in elderly male patients, with the goal of optimizing therapeutic strategies for this population.MethodsA retrospective analysis was conducted on 89 elderly male osteoporosis patients treated at Sheyang County People’s Hospital from March 2023 to March 2024. Patients were allocated to two treatment arms based on the treatment regimen they received: the denosumab group (n = 49) and the ZA group (n = 40). Adverse drug reactions (e.g., myalgia, flu-like symptoms, and back pain) were recorded, and changes in bone metabolism markers and bone mineral density (BMD) at the lumbar spine (L1-L4), femoral neck, and total hip were evaluated after 1 year of treatment.ResultsAfter 1 year of treatment, BMD of lumbar spine significantly increased in both groups (P < 0.05), with the denosumab group showing a greater improvement (0.41 ± 0.68 vs. 0.14 ± 0.86, P = 0.037). In contrast, the ZA group demonstrated superior efficacy in BMD of femoral neck (P = 0.011) and total hip (P = 0.029). Adverse reactions occurred in 15 patients: 2 in the denosumab group (muscle pain) and 13 in the ZA group (10 flu-like symptoms, 2 muscle pain, and 1 back pain). The incidence of flu-like symptoms was significantly higher in the ZA group (32.5% vs. 0%, P < 0.001).ConclusionDenosumab demonstrated superior efficacy in reducing fracture risk at the lumbar spine, while ZA showed greater protective effects at the hip. Although both agents significantly improved bone metabolic parameters, denosumab exhibited a more favorable safety profile in clinical application.